Ecological aspects of larval incidence of mosquitoes (Diptera: Culicidae) in Tuxpan, Veracruz, Mexico - DE LA CRUZ-FRANCISCO, VICENCIO; VEDA-MORENO, DALIA IBETH; VALDÉS-MURILLO, ARTURO (Revista Colombiana de Entomología, 2012)
Was characterized the Culicidae family of the region of Tuxpan, Veracruz. For this purpose, four sectors were established: Colonia Reyes Heroles, Colonia Libertad, Colonia Infonavit Puerto Pesquero and Colonia La Mata de Tampamachoco. From May to November 2009 three sampling were made in each sector placing larvitraps randomly in homes and in natural environments, as complement were done focal samplings for the organisms’ collection in recipients with cumulative water. By sector there were estimated the wealth, abundance, diversity of Shannon, Pielou equity, Simpson’s dominance, and the similarity between seasons. Considering the four locations, 5,645 were captured culicids larvae, determining five genera and 14 species. In order of importance the most abundant species in this study were: Aedes aegypti with 2,016 specimens, Ochlerotatus taeniorhynchus with 1,598, Aedes albopictus with 1,465. Puerto Pesquero showed the highest species richness and abundance. The diversity and equity were higher in the La Libertad, whilst the town Puerto Pesquero showed greater dominance. The communities of culicids are similar among the urban sectors but are different with the periurban sectors this reveals that the physical characteristics of the suburbs define the communities of culicids existing greater diversity and abundance in areas that offer the necessary conditions for their proliferation as the natural spaces that offer the periurban areas.